Analysis of the Fiqh Curriculum in Modern Islamic Boarding Schools (Boarding Schools) - Mulyawan Safwandy Nugraha; Miska Unil Ilma (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Fiqh is an element of the Islamic Religious Education curriculum both in schools and madrasas. At school, PAI learning requires a time allocation of 2 JP, which ideally would not be enough to achieve learning objectives. But for boarding school-based schools, PAI learning, especially fiqh, gets its own allocation, both in the form of learning outside of school and in the form of programs in dormitories. The aim of this research is to analyze the fiqh curriculum, especially in boarding school-based schools, using a qualitative case study approach. The conclusion that can be drawn from this research is that the fiqh curriculum which is integrated with the school curriculum at Riyadhul Jannah Modern Middle School has more benefits than being able to cover deficiencies in learning allocation at school, the Islamic boarding school curriculum can also directly ensure the practice of fiqh in students' daily lives with the help of The supervisor or guardian of the room. The role of Fiqh learning in the dormitory, even though it uses conventional learning by reading the yellow book and the teacher explaining it, actually makes learning more effective and efficient because students and teachers have more freedom in explaining or raising topics related to deficiencies or problems in the field of daily worship. (contextual).